2023
DOI: 10.1111/papr.13302
|View full text |Cite
|
Sign up to set email alerts
|

Fatty infiltration of the erector spinae at the upper lumbar spine could be a landmark for low back pain

Murat Şakir Ekşi,
Emel Ece Özcan‐Ekşi

Abstract: PurposeIntervertebral disc degeneration (IVDD), Modic changes, and fatty infiltration in the paraspinal muscles are possible causes of low back pain (LBP). Multifidus has been the most commonly blamed paraspinal muscle in the etiology of LBP. However, it contributes to 20% of the extensor moment on the lumbar spine. In the present study, we aimed to identify whether patients with LBP and asymptomatic subjects differed in terms of intervertebral discs, end‐plates, and fatty infiltration in their paraspinal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Our findings confirmed the findings of Ding et al [18], as they concluded that erector spinae tended to maintain the spinal sagittal balance and when erector spinae could not properly contract, subjects with lumbar spondylolisthesis might become surgical candidates. A recent case-control study comparing subjects with LBP and those without LBP reported that fatty infiltration in the erector spinae at upper lumbar spine was the main predictor for LBP [59]. Fatty infiltration impairs the quality of the paraspinal muscles since fat tissue is noncontractile [60][61][62].…”
Section: Does Radiology Correlate With Clinical Findings?mentioning
confidence: 99%
“…Our findings confirmed the findings of Ding et al [18], as they concluded that erector spinae tended to maintain the spinal sagittal balance and when erector spinae could not properly contract, subjects with lumbar spondylolisthesis might become surgical candidates. A recent case-control study comparing subjects with LBP and those without LBP reported that fatty infiltration in the erector spinae at upper lumbar spine was the main predictor for LBP [59]. Fatty infiltration impairs the quality of the paraspinal muscles since fat tissue is noncontractile [60][61][62].…”
Section: Does Radiology Correlate With Clinical Findings?mentioning
confidence: 99%
“…In their 2023 publication, Murat et al concluded that the erector spinae (ES) had a greater contribution to lumbar extension compared to the multifidus. Therefore, its contribution to low back pain would also be greater [ 34 ].…”
Section: Introductionmentioning
confidence: 99%